Analysis Of Human Computer Interaction Approach In Pospay Application - Nur Azis; Efendi; Azizah Silfa Azzahra; Arianto Muditomo; Agustina (Institute of Computer Science (IOCS), 2022)
Fulfillment of customer service is the company's priority in developing a digital service platform. Digital services with many users accessing, of course, require service applications to be able to be used optimally. Human-Computer (HCI) analysis, by focusing on usability aspects which include learnability, efficiency, memorability, errors, and satisfaction aspects, can be an analytical approach from the user's side of an application so that the application can become an application that follows user needs. This study applies HCI analysis to the Pospay application with 100 community respondents using a simple random sampling technique. The analysis results, especially on the user side based on the opinions of user respondents, shows that the Pospay application has implemented aspects of learnability, effectivity, memorability, and satisfaction well but has several drawbacks of the error.